TreEAT trial: Protocol for a randomized controlled trial investigating the efficacy and safety of early introduction of tree nuts for the prevention of tree nut allergy in infants with peanut allergy. Issue 3 (16th March 2023) - McWilliam, Vicki L.; Koplin, Jennifer J.; Allen, Katie; Robinson, Marnie; Smart, Joanne; Loke, Paxton; Peters, Rachel L.; Dang, Thanh; Lee, Katherine J.; Dalziel, Kim; Tey, Dean; Taranto, Mark; et al.
Abstract: Introduction: Children with peanut allergy are at increased risk of developing tree nut allergies, which can be severe and for most lifelong. Introduction of peanut in the first year of life can reduce the risk of peanut allergy; however, prevention strategies for tree nut allergies have not been established. We aimed to test the efficacy and safety of a novel strategy, a supervised multi‐nut oral food challenge (OFC) compared with standard care for tree nut allergy prevention in infants at high risk of developing tree nut allergy, TreEAT. Methods and Analysis: TreEAT is a 2‐armed, open‐label, randomized, controlled trial (RCT). Infants ( n  = 212) aged 4–11 months with peanut allergy will be randomized 1:1 at peanut allergy diagnosis to either a hospital‐based multi‐tree nut (almond, cashew, hazelnut, and walnut) OFC using multi‐nut butter or standard care (home introduction of individual tree nuts). All infants will be assessed at age 18 months, with questionnaires and SPT to peanut and tree nuts. Peanut and tree nut OFCs will be performed as required to determine the allergy status for each nut. The primary outcome is tree nut allergy at age 18 months. Secondary outcomes include peanut allergy resolution, proportion, and severity of adverse events related to tree nut ingestion, number and frequency of tree nuts ingested, quality of life and parental anxiety, and allergy‐related healthcare visits from randomization to 18 months of age. Analyses will be performed on an intention‐to‐treat basis. Ethics and Dissemination: TreEAT was approved by the Royal Children's Hospital Human Research Ethics Committee (#70489). Outcomes will be presented at scientific conferences and disseminated through publication. Trial Registration Number: ClinicalTrials.gov ID: NCT04801823.